Escala de depressão, ansiedade e estresse (DASS): adaptação e validação para o português do Brasil - Vignola, Rose Claudia Batistelli [UNIFESP] (2013)
Depression and anxiety are very common emotional disorders currently being stress increasingly pointed in the literature as a risk factor for these states. Although the relationship between depression, anxiety and stress is complex, studies show that phenomena are interconnected: transit between negative affect, emotional distress and physiological changes in the HPA axis. The objective of this study was to adapt and validate to the Portuguese of Brazil - DEPRESSION, ANXIETY AND STRESS SCALE, a 21-item short scale, The DASS-21 is a self-report scale with three subscales (depression, anxiety and stress). The DASS was administered to a sample of 242 outpatients (18 and 75 years), who was submitted to the Beck Inventory of Depression and Anxiety, and the Lipp Inventory too. The factorial analysis and distribution among the subscales indicated that the structure of three distinct factors is quite adequate, approaching more than originally proposed model, and legitimizing the nature of the scale, which is to evaluate three different emotional states. The KMO test (0.949) indicated a high model fit. The Internal Consistency - Cronbach Alpha - obtained for the Depression subscale was 0.92, for Stress was 0.90 and 0.86 for anxiety. The correlation of DASS21 with other scales was also high: DassDepressão / BDI 0.86; DassAnsiedade / BAI 0.80 and DassEstresse / Lipp 0.74. Thus, the values of Cronbach's alpha reliability of the DASS guarantee, as well as their correlations with the other scales studied also testify in favor of its validity. It can be used by different health professionals (physicians, nurses, social workers, nutritionists, physiotherapists), eliminating the use of multiple recurrent and different instruments to assess these states, reducing time and emotional investment of the subjects, as well as facilitating seeking earlier treatment. Questionnaire access link: http://www2.psy.unsw.edu.au/dass/Portuguese/Vignola-Tucci%20Brazilian%20Portuguese.htm